PENGARUH EDUKASI KESEHATAN TERHADAP TINGKAT PENGETAHUAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI PADA REMAJA PUTRI DI SMA KEBANGSAAN MEDAN - Ronika Siregar; Lenny Lusia Simatupang (Indonesian Trust Nursing Journal, 2026)
Breast cancer is one of the leading non-communicab le diseases with the highest incidence and mortality rates among women, including in Indonesia. The high mortality rate of breast cancer is largely attributed to delayed early detection. Breast Self-Examination (BSE) is a simple, low-cost, and self-performed early detection method that can be practiced from adolescence. However, the level of knowledge and awareness of adolescent girls regarding BSE remains relatively low, particularly due to the lack of structured health education in school settings. Therefore, health education is considered an important effort to improve adolescents’ knowledge and ability to perform BSE correctly. This study aimed to determine the effect of health education on the level of knowledge regarding Breast Self-Examination (BSE) among adolescent girls at SMA Kebangsaan Medan. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest method. The sample consisted of 45 adolescent female students selected through a total sampling technique. Data were collected using a BSE knowledge questionnaire administered before and after the health education intervention. Data were analyzed using univariate and bivariate analyses with the Wilcoxon test. The results showed that prior to the health education intervention, most respondents had a low level of knowledge about BSE. After the intervention, there was a significant improvement in knowledge levels, with the majority of respondents categorized as having good knowledge. The Wilcoxon test revealed a p-value of 0.001 (p < 0.05), indicating a significant effect of health education on increasing BSE knowledge. Health education has a significant effect on improving adolescent girls’ knowledge regarding Breast Self-Examination (BSE). Health education should be continuously integrated into school health programs as a promotive and preventive strategy for early detection of breast cancer. Further research is recommended to use a quasi-experimental design with a control group. In addition, it is necessary to add behavioral variables and demonstration assessments through observation to evaluate the consistency and skills of respondents in performing SADARI correctly.